(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Floating pills promote the distribution of drugs to the stomach, raise the absorption of pharmaceuticals, and extend their time in the body. With this objective, For the purpose of achieving this goal, floating tablets comprising an aqueous extract of liquorice andandXanthanGum were prepared and evaluated.Floating Herbal tablets increase bioavailability, speed up local medication distribution to the stomach, and extend the duration that pharmaceuticals remain in the stomach. For the treatment of stomach ulcers, floating tablets with liquorice alcohol extract as the primary active ingredient were created in this study. The tablets containing alcoholic liquorice extract, HPMC K100M, sodium bicarbonate, talc, and magnesium stearate were made utilising the direct compression technique. The physical characteristics of the tablets, such as their diameter, thickness, hardness, uniformity of weight, and buoyancy duration, were also assessed. Formulation was improved using buoyancy time.All tablet formulations had a buoyancy time of less than 2 minutes and maintained their floating state for the duration of the research, up to a maximum of 2 hours. The formulation with the best performance, f1, had a buoyancy time of 0.25 minutes.For gastro retentive drug delivery systems, a formulation including liquorice, sodium bicarbonate, and HPMC K100M can be promising.